Characteristics and formation mechanism of Carbonate buried hill fractured-dissolved reservoirs in Bohai Sea, Bohai Bay basin, China - Huang, Zhi; Yang, Haifeng; Ye, Tao; Deng, Hui; Guo, Jingzhen; Liang, Shuyi; Xiao, Shuguang; Ma, Cunfei (Frontiers in Earth Science, 2023)
Carbonate buried hill is an important domain with exploration breakthrough made recently in the Bohai Sea, the Bohai Bay Basin, China. However, the buried hill reservoirs are highly heterogeneously and their plane distribution remains unclear, which restrict the subsequent exploration. Taking CFD2 oilfield as an example, based on core, thin section, seismic and well logging data, the characteristics of carbonate buried hill reservoirs in the study area were clarified, the formation mechanism of the reservoirs was discussed, and the development model of the reservoir was established. The results show that the carbonate buried hill reservoirs in the study area are mainly fractured-dissolved reservoirs, and the formation of the reservoirs is mainly related to structural fractures and fluid dissolution along the fractures. The structural fractures are found mainly in two groups: NWW and NEE, by trending. The C and O isotope values reveal that the diagenetic fluid is mainly atmospheric fresh water. The NWW-trending structural fractures were formed under the control of the Indosinian compression, and the NEE-trending structural fractures were formed under the control of the Yanshanian strike-slip transpression. Dolomite is more brittle than limestone and is the main lithology for forming effective fractures. Structural fractures provide favorable channels for atmospheric water dissolution. The C and O isotope values reveal that at least two stages of dissolution have occurred in the study area. The first stage is supergene karstifiction, when fine-silty crystal carbonate was mainly filled, with the C isotope between -2‰ and 0‰ and the O isotope between -16‰ and -8‰. The second stage is burial karstification, when coarse crystal carbonate was mainly filled, with the C isotope between -4‰ and -2‰, the O isotope between -18‰ and -8‰, and a higher diagenetic temperature. A model of fractured-dissolved reservoir under the control of "structure-lithology-fluid" was established. This model highlights that the structural fractures formed by tectonic activities are crucial to reservoir development, and lithology is the internal factor controlling reservoir distribution. Dolomite exhibits the compressive strength only half of limestone, and it is the dominant lithology for reservoir development.